Poetyki lingwistyczne - Kluba, Agnieszka (Przestrzenie Teorii, 2007)
The work focuses on recognising the features of each individual language-centered poetics, referring to different philosophies and aesthetics. For instance "impeaching the language" (the first generation of linguistic writers) involves opposite results to the imperative "to protect my own language from fabrication and depravation" (New Wave linguistic poets). The opposition "trustfulness-distrustfulness" does not cover all possible complications within the realm of poetic metareflection. Having different opinions about the effectiveness of their own interventions into language these reflections are located between poetical optimism and pessimism. The latter is highly related to what is called "the crisis of language". The work investigates the role of post-war linguistic poetry in breaking down the conventional optimism of Polish "avant-garde poetic model", not matching up to the European poetry signed with the names of Mallarmé, Klebnikov, George, Celan and the others.